Thaumatophyllum calcicola a new deciduous species of Araceae from limestone outcrops in Brazilian Cerrado - Pereira, Anderson; Sakuragui, Cássia Mônica; Coelho, Marcus A. Nadruz; Rando, Juliana Gastaldello (Phytotaxa, 2026)
Thaumatophyllum calcicola, a new species of Araceae restricted to limestone outcrop vegetation within the Brazilian Cerrado (savanna) in the western region of the state of Bahia, is described and illustrated, and compared with the morphologically similar species Thaumatophyllum speciosum.